An Assessment of the Impact of a COMESA Customs Union - Sawkut, Rojid; Boopen, Seetanah (2012)
The Common Market for Eastern and Southern Africa (COMESA) launched its free trade area (FTA) on 31 October 2000 and is in the process of forming a custom union. A Common External Tariff (CET) with respect to all goods imported into the member states from third countries shall be established and maintained. The purpose of this study is three-fold. The first purpose is to assess the impact of the CET. Here we lowered only external tariffs to all regions leaving tariffs within COMESA as they are now to reflect the real situation. In this scenario, we take into consideration sensitive products which COMESA members might want to exclude from the CET to protect their markets. The second purpose is to implement the COMESA FTA fully. That is, to remove tariff on trade within COMESA states totally. This part of the study will give us an idea on whether countries within COMESA are losing by not implementing the FTA and if so, by how much. The third purpose is to assess the impact of the CET in a fully operational COMESA FTA. The methodology used for this analysis is a Computable General Equilibrium (CGE)--more specifically the Global Trade Analysis Project (GTAP) framework is used. Two standard GTAP closures have been modified to more realistically represent the African economies, namely the employment closure and the trade balance closure.